The homogenization method in the problem of a spherical layered elastic composite hollow - Toan, Pham Thi (Vietnam Journal of Mechanics, 1997)
In this paper, by using the homogenization method for the partial differential equations we study the statics and dynamics problems of a spherical layered elastic composite hollow. We can determine the approximate solution with an arbitrary accuracy, by solving a recurrent series of problems with homogeneous material, where the solution of problem in zero degree (the effective modulus theory) is initial data.